HUBUNGAN LAMA PENGOBATAN TBC DENGAN TINGKAT STRES PENDERITA TBC DI PUSKESMAS TAMBELANGAN KABUPATEN SAMPANG - Zahroh, Chilyatiz; Subai?ah, Subai?ah (Jurnal Ilmiah Kesehatan, 2016)
The Long-term medication of the timely tuberculosis sufferers makes them bored of taking medicines and control. As a result, the treatment were not successful and takes much longer. This situation makes TB sufferers stress. The purpose of this study was to find out the correlation between the long treatment of tuberculosis with the stress level of tuberculosis sufferers in Puskesmas Tambelangan, located in Sampang. The design of study was analytic-cross sectional. The population involved all of TB sufferers, totally 41 respondents, in wich 39 respondents were taken as the samples by using simple random sampling technique. The independent variables was long treatment of tuberculosis, whereas the dependent variables was stress levels. The data Collection was done by using questionnaires and medical records document TBC, Moreover, the data were analyzed by using Spearman rank test. The results showed the majority (57.7%) of respondents in the health centers are undergoing treatment in Puskesmas Tambelangan category 1 and nearly half (38.5%) of respondents in Puskesmas Tambelangan experiencing moderate stress. Furthermore, Based on the result obtained Spearman rank, it showed that ? (0,000) <? (0.05) so that there was a correlation between the long treatment of tuberculosis with the stress level of tuberculosis sufferers. The conclusions of study was that the longer treatment of tuberculosis, the more severe the stress level of tuberculosis sufferers. Therefore, the health workers are Expected to health workers to teach stress management in tuberculosis sufferers. So that tuberculosis sufferers who run the treatment did not experience stress.